Exploring Human Resource Management Practices in NGOs: A Case Study of Vavuniya District - Mangaleswaran, T. (Vavuniya Campus of the University of Jaffna, 2009)
The present study focuses on Exploring Human Resource Management Practices in NGOs: A Case Study of Vavuniya District. The literature review expresses that HRMP have been studied extensively among manufacturing, service and small medium enterprises. Even these researchers have not explored and compared HRMP in NGOs between Local and International. Therefore, this study attempts to fulfill the above gap. The HRMP comprises staffing, training, compensation, performance appraisal, employee relations and Human Resource Planning for this study. This study should be important to the NGOs industry because one of the major inputs to the NGOs is the HR and they spend a huge amount of money on HR/annum. If the HR is properly managed, they can achieve their objectives. The NGOs survival and effectiveness is important to rehabilitate and develop the people of the area.Two INGOs are selected such as Oxfam GB and Danish Refugee Council and two LNGOs are selected such as Social Economical and Environmental Developers (SEED) and Rural Development Foundation (RDF) for this study. An in-depth study of sampled organizations was made through reviewing literature available on profile etc. of these organizations, collecting primary data and information by holding face to face structured interviews and discussions. The interviews involved the use of a set of predetermined questions and highly standardized techniques of recording. The selected NGOs are practicing the main HRM functions to manage their organizations successfully. This study also identifies importance of HRM practices in NGOs and what is the difference between INGOs and LNGOs in practicing HRM. Therefore, NGOs success and survival mainly depend on Human Resources, which is major resource to be managed effectively.
Keywords: Human Resource Management; Non Governmental Organizations; Service Organization